پاکستان میں معروف فیمنسٹ وومن اداروں کا تعارفی جائزہ: An Introductory Review of Leading Feminist Women's Organizations in Pakistan - Zoha Fatima; Dr Malik Kamaran (International Research Journal of Arabic and Islamic Studies, 2023)
Pakistan is a multi-national society in which various movements and nations are living and all these classes are engaged in their own efforts to promote their thoughts. There are movements and institutions related to women's rights among them. They take measures for rights and bring their problems to the authorities and strive for their solution. The objectives of these organizations include not only the protection of women's family rights but also the development of girls and young women. It also includes raising voice for their economic, social, political and moral rights and taking steps to solve them. Factories are also included for resources which solve the economic problems of women by providing employment. Similarly, these institutions also organize educational institutes in which free education is provided for women of all classes of Pakistan. In the article under review, an introductory review of active feminist organizations in Pakistan has been taken